Choosing the Right Proverbs for the theme "at the Doctor" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Proverbs are a powerful linguistic tool that can convey wisdom and cultural values succinctly. In the context of medical consultations, using appropriate proverbs can enhance communication and understanding between doctors and patients. This article explores the selection and application of suitable proverbs for the theme "At the Doctor." Through a detailed literature review and qualitative analysis, the study identifies key proverbs that are most effective in medical settings, examines their cultural significance, and discusses their impact on doctor-patient interactions.